The Existence of The Role of The Financial Auditing Agency in Enforcing State Financial Accountability as The Supreme Audit Institution in Indonesia - Mardiana, Mardiana; Saputri, Syabila; Purwanto, Purwanto (PT. Hafasy Dwi Nawasena, 2025)
This study reviews the position and role of the Supreme Audit Agency (BPK) in ensuring the enforcement of state financial accountability as the highest audit institution in Indonesia. The main focus of this study lies on the historical, constitutional, and institutional dynamics that have shaped the existence of BPK since the early days of independence until after the amendment of the 1945 Constitution. The purpose of this study is to examine how the legal construction and institutional development of the BPK strengthen the state's external oversight function and ensure transparency and fiscal responsibility. This study uses a normative legal method with a juridical, conceptual, and case study approach, which is processed through analysis of regulations, doctrines, historical archives, and public audit practices. The results of the study show that the long journey of the BPK, starting from the legacy of the Algemene Rekenkamer, institutional transformation during various political periods, to harmonization with international audit standards, has formed a strong foundation for the independence and professionalism of the institution. However, challenges remain, particularly in harmonizing authority with other oversight actors and maintaining the orientation of audits in the strategic realm of state finances. This study confirms that the BPK plays an essential role as the guardian of national fiscal integrity and an important pillar in Indonesia's checks and balances architecture.